2016
DOI: 10.1159/000447695
|View full text |Cite
|
Sign up to set email alerts
|

Shortened Activated Partial Thromboplastin Time May Help in Diagnosing Hereditary and Acquired Angioedema

Abstract: Objective: To evaluate whether activated partial thromboplastin time (APTT) could be used in the laboratory diagnosis of hereditary or acquired angioedema (HAE or AAE) with and without C1 inhibitor (C1-INH) deficiency. Methods: In a prospective investigation, APTT and other coagulation parameters were determined in 149 adult patients with various types of angioedema and in 26 healthy participants (HP). Results: Mean APTT was significantly shortened in HAE-C1-INH type I (p < 0.0001) and type II (p = 0.0017) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…D-dimers, which are widely available, have been reported to be elevated in acute hereditary angioedema attacks (Reshef et al, 2015), but they are nonspecific and there are no formal analyses of sensitivity or specificity in this context. A shortened activated partial thromboplastin time, which is rapidly and widely available, may help to diagnose HAE-C1-INH and AAE-C1-INH when determination of C1-INH is not available (Bork and Witzke, 2016).…”
Section: Hereditary Angioedema With Normal C1-inhmentioning
confidence: 99%
“…D-dimers, which are widely available, have been reported to be elevated in acute hereditary angioedema attacks (Reshef et al, 2015), but they are nonspecific and there are no formal analyses of sensitivity or specificity in this context. A shortened activated partial thromboplastin time, which is rapidly and widely available, may help to diagnose HAE-C1-INH and AAE-C1-INH when determination of C1-INH is not available (Bork and Witzke, 2016).…”
Section: Hereditary Angioedema With Normal C1-inhmentioning
confidence: 99%
“…Recently, Bork and Witzke [48] showed that a shortened activated partial thromboplastin time (aPTT) may help to diagnose C1-INH-HAE and C1-INH-AAE when other tests are not available. aPTT is a routine and easy screening test for the "intrinsic" and "common" pathways of blood coagulation [49].…”
Section: Diagnosismentioning
confidence: 99%
“…Moreover, serum C1q assessment aids the early differentiation between AAE and HAE [52] . Recent evidence suggests novel laboratory methods for the differential diagnosis of AAE and HAE when the determination of C1-INH is not yet available [56] . There is widespread agreement on therapeutic goals (i.e., to reduce mortality and morbidity, reduce the frequency of attacks, improve quality of life, and train patients in selfadministration) in C1-INH-related AE whereas no guidelines are available concerning the treatment of ACEI-RA and I-AAE [22,23,[57][58][59] .…”
mentioning
confidence: 99%